If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + -14 = 3(x + -4) Combine like terms: 32 + -14 = 18 18 = 3(x + -4) Reorder the terms: 18 = 3(-4 + x) 18 = (-4 * 3 + x * 3) 18 = (-12 + 3x) Solving 18 = -12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 18 + -3x = -12 + 3x + -3x Combine like terms: 3x + -3x = 0 18 + -3x = -12 + 0 18 + -3x = -12 Add '-18' to each side of the equation. 18 + -18 + -3x = -12 + -18 Combine like terms: 18 + -18 = 0 0 + -3x = -12 + -18 -3x = -12 + -18 Combine like terms: -12 + -18 = -30 -3x = -30 Divide each side by '-3'. x = 10 Simplifying x = 10
| -29+7x=-5(1-2x) | | 12x=6x+24 | | 12x=5x+24 | | 8y+2-6y=3+t-10 | | 5(3x-1)-3=25+4x | | z+2z= | | 12+3= | | -3x-8(1+x)=-2x+37 | | -9p(-6p+2)=-2p-9 | | 5(3z+7)=125 | | 1=12x^2+11x | | 15x^2-13x=0 | | 7x-6x=13+3x | | 5x^2-3x=8 | | 6x+8-2x(7-2)=2(6x+1) | | 4x^3-2x^2+12x=0 | | 2x^2=16x | | 36-6x=28 | | (x-9)(3x+1)=0 | | 3(4y+5)=51 | | 6(2g-5)=-6 | | x^2+9=6x | | 8x+16=2x+106 | | 2y+10=5y-4 | | 14x^2=0 | | 110-5x=22x+20 | | x(x+7)=15x-21 | | 21=1-5p | | 5=3+8b | | 11-10x=85-24x | | 10-2y=y+8 | | 6x*x+35x+48=x |